Utilization Of New Media As A Means Of Learning During The Covid-19 Pandemic At The University Level In Students' Perspectives - Muhammad Aidil Ghunaya Said (Pena Cendekia Insani, 2021)
The idea of ??this paper is to start from a learning problem in online classes that still looks only one way or commonly called lectures, questions and answers, and group discussions. While the development of technology at this time is very sophisticated and modern, it can accelerate the dissemination of information in just seconds. The goals and targets to be achieved are to realize a learning based on the use of new media as a means of learning models that meet the needs of students to be actively involved in learning. The research method that the researcher uses is qualitative with the selection of 4 student/I informants as key informants. Data collected through in-depth interviews using interview guidelines in order to remain in the focus of research and the data obtained were analyzed through three paths, namely data reduction (selection process, simplification, interview results), data presentation and conclusion drawing. The results of this study can be concluded that there are obstacles, shortcomings and advantages that affect the learning process through the use of New Media as a new learning medium during the Covid-19 pandemic.